Hematological and Immunological Alterations, in Individuals, with Typhoid Fever; an Investigation Comparing CCL5 and IgA Levels Using ELISA Assays - Abdulameer, Ali Nahedh; Dakheel, Alaa Haider; Hussain, Aya Ali; Hashim, Ayat Hameed; Abdulkareem, Ammna Ali; Jaber, Baneen Haider; Hadi, Fatima Mansoor; Aziz, Dhifaf Zeki (Journal of Science in Medicine and Life, 2024)
Typhoid fever continues to be a public health concern, in parts of the world caused by Salmonella enterica subspecies I serovar Typhi. The objective of this study was to investigate whether there are any changes in immunological parameters among individuals with typhoid fever. This research was conducted as a case control study in September 2022. A total of 30 adults (above 15 years old) diagnosed with typhoid fever were included, alongside a number of adults for comparison. In this study we examined the levels of human CCL5 Elisa and human IgA. Out of the patients 87.50% tested positive for IgM antibodies while 18.75% showed positivity for both IgM and IgG antibodies; intriguingly only one sample displayed positivity solely for IgG antibodies. Moreover, compared to the control group TG levels were significantly increased LDL levels exhibited an increase but not significantly different from control values (whereas HDL levels were notably decreased). Additionally, both CCL5 and IgA showed elevations, in patients compared to the control group.